The role of cryptic dispersal in shaping connectivity patterns of marine populations in a changing world. (2nd March 2017) - David, Andrew A.; Loveday, Benjamin R.
Abstract : Genetic connectivity directly shapes the demographic profile of marine species, and has become one of the most intensely researched areas in marine ecology. More importantly, it has changed the way we design and describe Marine Protected Areas across the world. Population genetics is the preferred tool when measuring connectivity patterns, however, these methods often assume that dispersal patterns are (1) natural and (2) follow traditional metapopulation models. In this short review, we formally introduce the phenomenon of cryptic dispersal, where multiple introductory events can undermine these assumptions, resulting in grossly inaccurate connectivity estimates. We also discuss the evolutionary consequences of cryptic dispersal and advocate for a cross-disciplinary approach that incorporates larval transport models into population genetic studies to provide a level of oceanographic realism that will result in more accurate estimates of dispersal. As globalized trade continues to expand, the rate of anthropogenic movement of marine organisms is also expected to increase and as such, integrated methods will be required to meet the inevitable conservation challenges that will arise from it.